2020
DOI: 10.1002/jts.22540
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation in a Veterans Affairs Residential Posttraumatic Stress Disorder Treatment Setting: The Roles of Thwarted Belongingness and Perceived Burdensomeness

Abstract: Suicide is a significant public health concern, and, specifically, the veteran population has exhibited a 22% higher risk of death by suicide than the general population (Department of Veterans Affairs, 2017). The interpersonal psychological theory of suicide (IPTS; Joiner, 2005) appears to be the most widely researched theory to examine factors associated with suicidal ideation. The IPTS applies to veteran suicidal ideation in that veterans may feel they are burdensome to others or that they do not belong fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
(84 reference statements)
3
6
0
Order By: Relevance
“…In contrast, and consistent with previous studies, Martin et al. (2021) found that only perceived burdensomeness was a meaningful predictor of suicide risk among veterans with posttraumatic symptoms. They also provide a foundation for understanding why perceived burdensomeness is not only frequently encountered in military samples but is also such a potent predictor of suicide risk given military institutional values that emphasize selfless service, self‐sufficiency, and courage, along with how effective and efficient it can be to target these identity‐based beliefs in treatment.…”
supporting
confidence: 86%
“…In contrast, and consistent with previous studies, Martin et al. (2021) found that only perceived burdensomeness was a meaningful predictor of suicide risk among veterans with posttraumatic symptoms. They also provide a foundation for understanding why perceived burdensomeness is not only frequently encountered in military samples but is also such a potent predictor of suicide risk given military institutional values that emphasize selfless service, self‐sufficiency, and courage, along with how effective and efficient it can be to target these identity‐based beliefs in treatment.…”
supporting
confidence: 86%
“…Although the interaction term was non‐significant for non‐normal PB and in the model with LSB, it was significant above and beyond anxiety and depression for PB n . Several previous studies reported a non‐significant interaction term (Bodell, Smith, & Witte, 2020; Ma et al, 2016; Martin, Pukay‐Martin, Blain, Dutton‐Cox, & Chard, 2020; Roeder & Cole, 2019), and some indicated it to be significant (Horton et al, 2016; J. D. King et al, 2018). Specifically, in the current study, the NJ plot pinpointed the fact that where PB was extremely high, the effect of TB‐7 elevated significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Shame also may be an expression of betrayal trauma, theorized as an adaptive response to maintain relationships, such as instances where MST victims are required to collaborate with or depend on perpetrators (Freyd, 1994;Platt et al, 2017). Last, shame also contributes to thwarted belongingness, a recognized risk factor of suicidal ideation; this may explain findings that indicate that unwanted sexual experiences during military service had a stronger relationship with suicide risk for men as compared to women (Bryan et al, 2015) as well as other research that showed the association of shame and suicidal ideation among female MST survivors (Monteith et al, 2017; see also : Cunningham, 2019;Joiner et al, 2005;Rogers et al, 2017; for an exception to this finding see: Martin et al, 2020).…”
Section: Introductionmentioning
confidence: 94%